Hematological Findings in COVID-19 Patients at Birat Medical College Teaching Hospital - Singh, Mrinalini; Kafle, Santosh Upadhyay; Parajuli, Surya B; Kafle, Neeta; Sinha, Amrita; Singh, Randhir Kumar (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION The outbreak of 2019 novel corona virus has also affected the Nepalese population. Real Time-Polymerase Chain Reaction (RT-PCR) is the diagnostic laboratory test for confirming the diagnosis. The complete blood count (CBC) is the laboratory test routinely done in patients suffering from any type of infection. This test provides the information to physicians regarding the inflammatory process. The objective of this study was to evaluate and find out whether hematologic parameters are affected in a person suffering from Covid-19 infections. MATERIAL AND METHODS This is a prospective study done from 3rd December 2020 to 3rd February 2021 for a period of two months. All the confirmed patients of corona (COVID-19) with RT-PCR, between days-1 to day-15 of PCR positivity, whose hematological profile was sent to the pathology laboratory department, were studied. The hematologic parameters studied include total white blood cells count (TLC), differential white blood cell count (DLC), hemoglobin and platelet counts. RESULTS Out of one hundred (100) RT-PCR positive patients eighty (80%) were male and twenty (20%) were female. Age group of patients ranged from 27 years to 94 years. Ninety-four (94%) patients reveal leukocytosis and Ninety-six (96%) patients showed increased in differential neutrophil count. Fifty-two (52%) patients reveal anemia and platelets count was normal in seventy-eight (78%) cases. CONCLUSION Covid-19 infection causes changes in the hematological parameters. Study of these parameters provides significant clinical information.